cGMP-Dependent Protein Kinase Inhibitors in Health and Disease - Jens Schlossmann; Johannes P. Huettner; Stefanie Wolfertstetter (MDPI AG, 2013)
cGMP-dependent protein kinases (PKG) exhibit diverse physiological functions in the mammalian system e.g., in vascular and gastrointestinal smooth muscles, in platelets, in kidney, in bone growth, nociception and in the central nervous system. Furthermore, PKG were found in insects and in the malaria parasite Plasmodium falciparum. Two different genes of PKG exist: a) the PKG-I gene that is expressed as cytosolic PKG-Iα or PKG-Iβ isoform, and b) the PKG-II gene, which expresses the membrane associated PKG-II protein. The enzyme kinetics, the localization and the substrates of these PKG enzymes differ utilizing different physiological functions. Various inhibitors of PKG were developed directed against diverse functional regions of the kinase. These inhibitors of PKG have been used to analyse the specific functions of these enzymes. The review article will summarize these different inhibitors regarding their specificity and their present applications in vitro and in vivo. Furthermore, it will be discussed that the distinct inhibition of the PKG enzymes could be used as a valuable pharmacological target e.g., in the treatment of cardiovascular diseases, diarrhea, cancer or malaria.